Insights into xanthomonas axonopodis pv. citri biofilm through proteomics - Zimaro, Tamara (BioMed Central, 2013)
BACKGROUND: Xanthomonas axonopodis pv. citri (X. a. pv. citri) causes citrus canker that can result in defoliation and premature fruit drop with significant production losses worldwide. Biofilm formation is an important process in bacterial pathogens and several lines of evidence suggest that in X. a. pv. citri this process is a requirement to achieve maximal virulence since it has a major role in host interactions. In this study, proteomics was used to gain further insights into the functions of biofilms. RESULTS: In order to identify differentially expressed proteins, a comparative proteomic study using 2D difference gel electrophoresis was carried out on X. a. pv. citri mature biofilm and planktonic cells. The biofilm proteome showed major variations in the composition of outer membrane proteins and receptor or transport proteins. Among them, several porins and TonB-dependent receptor were differentially regulated in the biofilm compared to the planktonic cells, indicating that these proteins may serve in maintaining specific membrane-associated functions including signaling and cellular homeostasis. In biofilms, UDP-glucose dehydrogenase with a major role in exopolysaccharide production and the non-fimbrial adhesin YapH involved in adherence were over-expressed, while a polynucleotide phosphorylase that was demonstrated to negatively control biofilm formation in E. coli was down-regulated. In addition, several proteins involved in protein synthesis, folding and stabilization were up-regulated in biofilms. Interestingly, some proteins related to energy production, such as ATP-synthase were down-regulated in biofilms. Moreover, a number of enzymes of the tricarboxylic acid cycle were differentially expressed. In addition, X. a. pv. citri biofilms also showed down-regulation of several antioxidant enzymes. The respective gene expression patterns of several identified proteins in both X. a. pv. citri mature biofilm and planktonic cells were evaluated by quantitative real-time PCR and shown to consistently correlate with those deduced from the proteomic study. CONCLUSIONS: Differentially expressed proteins are enriched in functional categories. Firstly, proteins that are down-regulated in X. a. pv. citri biofilms are enriched for the gene ontology (GO) terms ‘generation of precursor metabolites and energy’ and secondly, the biofilm proteome mainly changes in ‘outer membrane and receptor or transport’. We argue that the differentially expressed proteins have a critical role in maintaining a functional external structure as well as enabling appropriate flow of nutrients and signals specific to the biofilm lifestyle.